Self Efficacy Associated with Nurse Caring Behavior in Nursing Services in Private Hospitals - Zahroh, Roihatul; Qomariah, Siti Nur; Ningsih, Sri Utami; Bakar, Abu (International Journal of Psychosocial Rehabilitation, 2020)
His study aims to explain the relationship between self-efficacy and the nurse's caring behavior in providing nursing services in hospitals. The caring behavior that nurses often do not do is to provide guidance, teaching, and health education to patients. Good nursing services, determined by nurses caring actions given to patients (satisfying or disappointing). Good nurse self-efficacy will increase nurses caring behavior. The research design used an analytical description with Cross-Sectional design. The population was all hospital nurses, samples were taken by 75 nurses with a purposive sampling technique. The sample criteria are nurses on duty in the hospital room with a minimum term of one year. Data self-efficacy and caring behavior are taken using a questionnaire and analyzed by using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results showed that self-efficacy was related to nurses caring behavior in nursing services at the hospital with a value of t= 8.108 ( ≥ 1.96 ). The results of measurement of voting behavior, an effort is done and endurance, thinking patterns and emotional reactions, and the embodiment of the skills possessed, the value of T-statistic indicators ≥1.96 which said indicators are statistically significant or valid forming factors or measuring factor variables self- efficacy. The factors forming nurses caring behaviors are Maintaining Belief, Knowing, Being With, Doing for, and Enabling (T-statistic ≥ 1.96). The conclusion is self-efficacy related to me at the nurse caring behaviors in the nursing services at the hospital. Future studies need to conduct experiments related to the training of self-efficacy to nurse caring behaviors.